Yemen : Air Transport Sector Strategy Note - Schlumberger, Charles (World Bank, Washington, DC, 2012)
Recent sector work on air transport in Yemen found the Yemeni air transport sector to be relatively small compared to that of other countries of similar size, population, and Gross Domestic Product (GDP). In 2007, the total air traffic was 1.8 million passengers, 76 percent being international travelers and 24 percent domestic travelers. Yemen counts three airports open to international services among a total of 18 civil airports; however, Sana'a is the only airport with significant traffic (80 percent of total passengers). The national legacy carrier, Yemenia, has operated all domestic and international routes since 1962. A second carrier, Felix, was established by private investors in 2008 with the objective to take over Yemenia's domestic network.